Empathy development through ESP: a Pilot Study - Anna O. Stebletsova; Irina Ivanovna Torubarova (LED Edizioni Universitarie, 2017)
The paper is devoted to ethical awareness which has become one of the main concerns in medical education and healthcare nowadays. The paper discusses empathy development in medical students as a significant element of their professional training. It is reported that empathy should be implemented in the academic curriculum of medical schools and universities as a part of a multidisciplinary approach. The authors argue that empathy could be developed in a foreign language classroom. They illustrate their statement by providing real class examples in which empathy-developing content is incorporated in English for specific purposes (ESP) for medical students. The students' empathy level was measured at the beginning and at the end of the course with a balanced emotional empathy scale (BEES) questionnaire. The analysis of the results of the comparative assessment indicate positive dynamics of empathy levels in the medical students tested, after the course was completed. The authors conclude that ESP can be effective in supporting and improving the required empathy levels of future healthcare workers to help them to deliver their humanitarian services successfully.